Penerapan Welch Power Spectral Density untuk Menilai Aktivitas Listrik Lambung terhadap Stimulasi Air Bersoda - Hidayatulail, Basitha Febrinda; Elta Sonalitha; Rizki Putri Intan Hafsari; Ananda Yoga Prasetya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines gastric slow-wave activity as recorded through electrogastrography (EGG), a non-invasive method for assessing gastric electrical rhythms that reflect underlying motility. Despite growing interest in understanding physiological responses to luminal stimuli, the specific spectral effects of carbonated water on Electrical Control Activity (ECA) remain underexplored, creating a gap in objective measurements of slow-wave modulation. The aim of this research is to evaluate how carbonated water influences dominant slow-wave frequency, power, and normogastric stability using a robust spectral estimation technique. A quasi-experimental pre–post design was conducted with ten healthy participants whose EGG signals were recorded across fasting, postprandial 1, and postprandial 2 phases. Signals underwent Butterworth filtering, Savitzky–Golay smoothing, and zero-phase processing before Welch Power Spectral Density (PSD) was applied to extract Dominant Frequency (DF), Dominant Power (DP), and Percent Normogastric Distribution (PND). Results showed a significant reduction in DF from fasting (0.049–0.050 Hz) to postprandial 1 (0.043–0.045 Hz, p < 0.05), while PND consistently declined across channels (fasting ≈63–65% vs. postprandial 1 ≈60–61% and postprandial 2 ≈62–63%, p < 0.05). DP exhibited an increasing trend, though only Channel 2 reached significance (p < 0.05). These findings indicate that carbonated water induces short-term modulation of slow-wave rhythmicity and redistributes spectral power away from the physiological 2–4 cpm band. In conclusion, carbonated water produces measurable alterations in gastric slow-wave activity, and Welch PSD proves effective for detecting subtle spectral changes in low-amplitude physiological signals.